A rare case of bilateral complex odontomas: Clinical, radiological and histopathological findings - Ozkan Miloglu; Ertan Yalcin; Saadetin Dagistan; Ibrahim Sevki Bayrakdar; Muhammet Calik; Umit Ertas (Wolters Kluwer Medknow Publications, 2014)
Odontoma is the most common odontogenic tumor that is radiographically and histologically characterized by the production of mature enamel, dentin, cementum and pulp tissue. It grows slowly and has nonaggressive behavior. This case report presents clinical, radiological and pathological findings of bilateral complex odontoma that is rarely in literature in a 30-year-old female patient.